2021
DOI: 10.1126/sciadv.abg0153
|View full text |Cite
|
Sign up to set email alerts
|

Multiple carbon incorporation strategies support microbial survival in cold subseafloor crustal fluids

Abstract: Biogeochemical processes occurring in fluids that permeate oceanic crust make measurable contributions to the marine carbon cycle, but quantitative assessments of microbial impacts on this vast, subsurface carbon pool are lacking. We provide bulk and single-cell estimates of microbial biomass production from carbon and nitrogen substrates in cool, oxic basement fluids from the western flank of the Mid-Atlantic Ridge. The wide range in carbon and nitrogen incorporation rates indicates a microbial community well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…Many studies estimate the biovolume of the measured cells from nanoSIMS images and apply literature values for the C density, or an empirical relationship between the C density and biovolume of phytoplankton cells (e.g., Verity et al, 1992 ; Stryhanyuk et al, 2018 ; Khachikyan et al, 2019 ), to approximate C f (e.g., Foster et al, 2013 ; Krupke et al, 2015 ; Schoffelen et al, 2018 ; Mills et al, 2020 ; Trembath-Reichert et al, 2021 ). Although this approach may yield a well-constrained value of C f , one must be careful when using it in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies estimate the biovolume of the measured cells from nanoSIMS images and apply literature values for the C density, or an empirical relationship between the C density and biovolume of phytoplankton cells (e.g., Verity et al, 1992 ; Stryhanyuk et al, 2018 ; Khachikyan et al, 2019 ), to approximate C f (e.g., Foster et al, 2013 ; Krupke et al, 2015 ; Schoffelen et al, 2018 ; Mills et al, 2020 ; Trembath-Reichert et al, 2021 ). Although this approach may yield a well-constrained value of C f , one must be careful when using it in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…The 8-Ma ridge flank system called North Pond on the Mid-Atlantic Ridge is one of the most extensively characterized oceanic crusts owing to data creation from time series metagenomic and metatranscriptomic analyses and bulk and single-cell metabolic rate measurements ( Trembath-Reichert et al, 2021 ). Despite the lack of inorganic electron donors, carbon fixation transcripts are associated with the highest rates of bicarbonate incorporation.…”
Section: The Oceanic Crust Biospherementioning
confidence: 99%
“… Trembath-Reichert et al (2021) hypothesized that both organic and inorganic carbon substrates are assimilated in the rocky subseafloor, which reflects the optimization of microbial communities to energy-limited conditions. Deep-sea dissolved organics may be largely oxidized for energy by organotrophic microorganisms, whereas bicarbonate may serve as a supplementary carbon source.…”
Section: The Oceanic Crust Biospherementioning
confidence: 99%
“…Several studies have revealed that the Earth’s living zone extends hundreds of meters if not tens of kilometers beneath the continents and the seafloor [ 58 , 59 ]. In these extreme environments, microbial life goes on slowly but surely, using metabolic processes such as carbon oxidation and methanogenesis [ 60 , 61 ]. That microbial cells thrive in sediments hundreds of meters below the seafloor and in Earth’s crustal rocks for more than a kilometer deep suggests various conceivable scenarios in which life could take a foothold and thrive in similarly harsh or harsher extraterrestrial habitats.…”
Section: Extant Mat Worlds In Ice and Rock Habitats—examples From Polar Lakes And Earth’s Deep Biospherementioning
confidence: 99%
“…Furthermore, so much of life in the biosphere is hidden from our senses below the surface and remains understudied in terms of their evolutionary, physiologic, biogeochemical, and biodiversity potential. For example, geothermal light fuels photosynthetic life in the deep sea [ 65 ], microbial life thrives beneath the vast Antarctic shelf [ 66 ], and life persists in the deep biosphere within sub-seafloor sediments and even the fluids within crustal rocks [ 60 , 61 ].…”
Section: Extant Mats and Microbialites As Testbeds For Study Of Extraterrestrial Lifementioning
confidence: 99%